FAKTOR YANG BERHUBUNGAN DENGAN KONSISTENSI PEMAKAIAN KONDOM PADA PEKERJA SEKS KOMERSIAL (PSK) DI EKS LOKALISASI PEMANDANGAN TELUK BETUNG SELATAN BANDARLAMPUNG - Prima Ardian; Rr. Tutik Sri Hariyati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Background: Nurses as health professionals are required to always keep and increase professionalism in order to provide quality nursing care. The purpose of this study to enhance the ability to evaluate the results of the reformer agencies in implementing the Discussion Case Reflection (DCR) in an effort to improve professionalism. Methods: The design was a pilot study involving the change agent is Head of Nursing and Coordinator of the Executive Unit. Sample selection is done by using purposive sampling. The sample was 26 nurses from nursing management 2, 4 head nurse and 20 nurses. Implementation of the renewal agency used an approach Plan, Do, Check, Act (PDCA). Results: The study carried out is guideline and standard operating procedures (SOP) about the DCR. Discussion Case Reflection guideline discusses the definition, purpose, benefits, roles and tasks as well as the implementation. Guideline and SPO are used as a reference implementation DCR in the room. Discussion Case Reflection helpful nurse in improving science, obtaining up to date research, solutions resolve service issues, raise awareness of quality practices and thinking critically. While the obstacles in the implementation of the limitations associated literature sources, execution time, the media and there are participants who are less active. Recommendations on the implementation of the DCR among others by conducting socialization to all the nurses, the need for library facilities in hospital and media DCR when the conduct of the DCR, flexibility of implementation time, making DCR one component Performance Indicators Individual, and implement DCR across inpatient and outpatient.